(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Objective: To assess perinatal outcomes in obstetric cholestasis and associate them with maternal obstetric and biochemical parameters. Study Design: A cross-sectional study Place and Duration: This study was carried out at Karachi Metropolitan University Abbasi Shaheed Hospital Karachi Pakistan between April 2025 to April 2026. Methods: 124 pregnant women diagnosed with obstetric cholestasis were included. Obstetric and biochemical parameters of the mother were documented, such as total bile acids, ALT, AST, GGT, and bilirubin. Perinatal outcomes measured were preterm labor, meconium-stained liquor, fetal distress, Apgar scores, admission to NICU, IUGR, respiratory distress syndrome, and stillbirth. Data were statistically analyzed using SPSS version 26, and associations were evaluated using appropriate tests (p<0.05). To assess ALT as a predictor of adverse perinatal outcomes, ROC curve analysis was performed. Results: Preterm birth rates were 40 cases (32.3%), meconium-stained liquor was seen in 36 cases (29.0%), and fetal distress was noted in 38 cases (30.6%). NICU admission was required in 34 neonates (27.4%), and low Apgar scores at 1 and 5 minutes were observed in 30 (24.2%) and 18 (14.5%) cases, respectively. IUGR was detected in 28 pregnancies (22.6%), and stillbirth was seen in 6 cases (4.8%). In the adverse outcome group, total bile acids (p < 0.05), ALT (p < 0.05), AST (p < 0.05), and GGT (p < 0.05) were all significantly elevated. ROC analysis demonstrated good predictive value for adverse outcomes with an AUC of 0.81, sensitivity of 78.2% and specificity of 72.5% for ALT ≥ 55 U/L. Conclusion: There is a significant association between obstetric cholestasis and adverse perinatal outcomes, and a close correlation between worsening biochemical parameters and fetal morbidity. ALT can be used as a supportive marker alongside bile acids to assist in risk stratification and improve antenatal management.